From Biological Control to Invasion: The Ladybird Harmonia Axyridis as a Model Species
DOI: 10.1007/978-1-4020-6939-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation involving Harmonia axyridis: a review of current knowledge and future perspectives

Abstract: 9 Abstract As an effective generalist predator of aphids and other hemipteran pests 10 H. axyridis has been a successful biological control agent. However, the very functional 11 traits that have contributed to its success in this regard also implicate it as an intraguild 12 predator that poses a significant risk not only to the diversity of other natural enemies of 13 Hemiptera (and their associated ecosystem services), but to biodiversity more widely. In 14 this paper we will specifically review the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
0
8

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 121 publications
1
141
0
8
Order By: Relevance
“…The wide diet breadth and recognition that H. axyridis is a top predator (Pell et al 2008) Chilocorus stigma (Say) (Colunga-Garcia, Gage 1998), followed more recently by a decline in 265…”
Section: Harmonia Axyridis and Declines Of Native Ladybirds 255 256mentioning
confidence: 99%
See 2 more Smart Citations
“…The wide diet breadth and recognition that H. axyridis is a top predator (Pell et al 2008) Chilocorus stigma (Say) (Colunga-Garcia, Gage 1998), followed more recently by a decline in 265…”
Section: Harmonia Axyridis and Declines Of Native Ladybirds 255 256mentioning
confidence: 99%
“…Such 307 interactions between drivers of change are undoubtedly important in population dynamics, and the 308 negative effects of H. axyridis are likely to be the result of a complex range of interactions and 309 processes including resource competition and intra-guild predation (IGP) (Majerus et al 2006). 310 The majority of research examining interactions between H. axyridis and other aphidophagous 321 species has focused on direct interference competition on other ladybirds, proposing that decline is 322 due to strong asymmetric IGP of eggs and larvae in favour of H. axyridis (Pell et al 2008 to the eggs of native species (Smith, Gardiner 2013). However, out of 342 attacks, video surveillance 328 illustrated that only two were attributable to alien ladybirds (H. axyridis feeding on conspecific eggs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brown et al (2011) showed evidence of a decline in the abundance of Adalia bipunctata (L.) (Coleoptera: Coccinellidae) in England and there has been a drop in frequency of A. bipunctata and Adalia decempunctata (L.) (Coleoptera: Coccinellidae) in Belgium (Adriaens et al 2010). Studies on intraguild interactions between H. axyridis and other aphid predators have been conducted under controlled conditions in laboratories and reveal predation of these other species by H. axyridis (Pell et al 2008). Although these laboratory bioassays enhance our understanding of possible IGP among aphidophagous species, it remains unclear whether the success of H. axyridis in the field can be attributed to a direct (e.g.…”
Section: Intraguild Predationmentioning
confidence: 99%
“…Avaliações sobre a sua competição com outros coccinelídeos, em laboratório, foram realizadas por Kajita et al (2000), Cottrell (2005), Pell et al (2008) e , que verificaram que sua atuação foi dominante em relação à Adalia bipunctata (L.), Coleomegilla maculata De Geer, Olla v-nigrum (Mulsant) e Propylaea japonica Thunberg, em razão do maior tamanho e da presença de estruturas protetoras como os espinhos dorsais ao longo do corpo das larvas.…”
Section: Introductionunclassified